Room One : A Mystery or Two. - Clements, Andrew (New York : Simon and Schuster Books for Young Readers, 2006)
A shrinking school in a dying town. A face in the window of an empty house. At first, these facts don't seem to be related. But Tead Hammond learns that in a very small town, there's no such thing as an isolated event.
3-6
Keywords: Mystery; Schools - Fiction